2018
DOI: 10.1111/ijfs.13741
|View full text |Cite
|
Sign up to set email alerts
|

Wheat preharvest herbicide application, whole‐grain flour properties, yeast activity and the degradation of glyphosate in bread

Abstract: Summary The aim of this study was to determine the effects of wheat preharvest application of a glyphosate‐based herbicide (Roundup WeatherMax® with Transorb® 2 Technology) on whole‐grain flour composition and properties, including yeast activity. The effect of dough fermentation on the degradation of herbicide residues was also estimated. Grain samples from two hard red spring wheat varieties exceeded the maximum residue limits (5 mg kg−1) in Canada. Glyphosate had minor effects on wheat kernels composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…This is consistent with most of the other studies published on the fate of glyphosate residues in grain-based foods. Gélinas et al (2018) did not observe any change in glyphosate concentration after baking fermented dough prepared from commercial flour fortified with glyphosate or a commercially available product containing glyphosate as the active ingredient. Gélinas et al did note an approximate 15% decrease in glyphosate concentrations observed in baked bread prepared from wheat grown in a field experiment and treated with a commercially available product containing glyphosate as the active ingredient, but they attributed this change to loss during sample extraction.…”
Section: Bakingmentioning
confidence: 65%
See 3 more Smart Citations
“…This is consistent with most of the other studies published on the fate of glyphosate residues in grain-based foods. Gélinas et al (2018) did not observe any change in glyphosate concentration after baking fermented dough prepared from commercial flour fortified with glyphosate or a commercially available product containing glyphosate as the active ingredient. Gélinas et al did note an approximate 15% decrease in glyphosate concentrations observed in baked bread prepared from wheat grown in a field experiment and treated with a commercially available product containing glyphosate as the active ingredient, but they attributed this change to loss during sample extraction.…”
Section: Bakingmentioning
confidence: 65%
“…Low et al (2005) reported baker's yeast reduced concentrations in glyphosate-fortified dough during the fermentation stage by 21%. Gélinas et al (2018) did not observe glyphosate degradation in glyphosate-fortified dough after fermentation, and there was no difference in glyphosate concentrations in yeasted and non-yeasted bread after baking.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In addition to treatments, baking quality traits were also impacted by cultivar and location, and as previously explained this could be due to changes in protein quality that is caused by genotypic and environmental effects. As Roisch and Lingens [19] and Gélinas et al [62] reported, glyphosate does not have a significant impact on yeast activity, and this may be the reason why most baking quality traits were not significantly affected by glyphosate.…”
Section: Effect Of Glyphosate On Baking Qualitymentioning
confidence: 95%